Epoxy Chromenes: The Therapeutic Agents from Flemengia strobilfera - Saxena, V.K. (Asian Journal of Chemistry, 2010)
New epoxy chromenes; flemingin X, Y and Z have been isolated from the leaves of Flemengia strobilifera. They have been identified by chemical and spectroscopic methods.